Drevesno-poljedelski podsistem na primeru protivetrnih pasov v Vipavski dolini - Premrl, Tine (Gozdarski vestnik, 2013)
The article discusses the silvoarable forestry subsystem as one of the agroforestry subsystems. For this purpose we focus on the windbreak practice we show on the example of the Vipava Valley. The article thus presents the issues of wind erosion in the Vipava Valley, foreign experiences with windbreaks are introduced, the basic principle of windbreak activities are explained, and the guidelines for their establishing are given at the same time.
Keywords: kmetijsko-gozdarski sistemi; drevesno-poljedelski sistemi; veter; burja; protivetrni pasovi; Vipava Valley; Vipavska dolina